Construção e validação de instrumento para avaliar a saúde da mulher na Atenção Primária - Araújo, Daísy Vieira de (2019)
The increase in women's life expectancy and population, associated with the broad expansion and strengthening of Primary Health Care contributes for new aspects of longitudinal and integral care to be outlined. In the interim, the construction and validation of an instrument with characteristics peculiar to the field of women's health, which can guide a good quality public assistance in primary health services in Brazil. This study aimed to gather validity evidence based on the test content, the response process validity, evidence based on the internal structure and reliability of the Women's Primary Health Care Assessment Instrument, to be used by health professionals and researchers to evaluate important indicators of women's health, and by the public management for planning and evaluating the actions directed towards the foregoing public. Therefore, a validation study was carried out The guidelines and methodology used are anchored in the Standards for Educational and Psychological Testing. The Women's Health Assessment Instrument in Primary Health Care presented psychometric properties of acceptable content validity and response process, which lays bare its conceptual and semantic quality, is valid and the responses are reliable for women in the 18-69 age range, since it is designed to assess women's health needs within the organizational logic of the Primary Health Care, considering the essential and derivative attributes.